Analisis Pangsa Pasar Beberapa Merek Produk Minuman Susu Fermentasi dalam Kemasan dengan Metode Rantai Markov di Lingkungan Kampus Universitas Udayana - Az-zahra, Keisa; Wiranatha, A. A. P. A. Suryawan; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 4 (2019): Desember, 2019)
The objectives of this research were to determine the consumer characteristics of fermented milk products, analysis market share of several packaged fermented milk brands at this time until next five years ahead and determine the long-term market balance at Udayana University. The data used in the study was primary data collected through a questionnaire, for analysis this research was using the markov chain method by software QM 5.3. The result of the characteristics consumers of fermented milk were dominated by women with an average age 21-25 years old and mostly profession are students, with an average spending money for snacks/drinks was Rp 100,000-300,000 /month with an average consumption of fermented milk 2-3 times/week. The reason of respondents consuming fermented milk was because of the taste was so special and respondents also get the information from advertisements on television, respondents usually buy the products from supermarkets on their own initiative by planning them first. The result of the research market share analysis was Yakult brand always leads market share, in the 2019 the Yakult brand was 55%, Cimory 30%, Calpico 8%, Vitacharm 4% and other brands 3%. in 2020 there was an increase for Yakult to 56%, a decrease for Cimory 29 .5%, Calpico 7.5%, Vitacharm 3.9% and other brands rising to 3.1%. In 2021 only for Yakult change to 56.1% and Vitacharm 3. 8%. In 2022 all brands were still in the same percentage but in 2023 Yakult change to 56 .2% and Vitacharm 3.7%. The market share will reach stable conditions where the market share of each brand was Calpico 7.0%, Cimory 25.7%, Vitacharm 3.4% and Yakult 60.6% and other brands 3.3%. Keywords : fermented milk, market share, markov chain method